Effects of Lysozyme, Proteinase K, and Cephalosporins on Biofilm Formation by Clinical Isolates of Pseudomonas aeruginosa. (8th February 2020) - Eladawy, Mohamed; El-Mowafy, Mohammed; El-Sokkary, Mohamed Mohamed Adel; Barwa, Rasha
Abstract : Pseudomonas aeruginosa is an opportunistic pathogen that can form biofilms, which confer resistance to immune clearance and antibacterial treatment. Therefore, effective strategies to prevent biofilm formation are warranted. Here, 103 P . aeruginosa clinical isolates were quantitatively screened for biofilm formation ability via the tissue culture plate method. The effects of lysozyme (hydrolytic enzyme) and proteinase K (protease) on biofilm formation were evaluated at different concentrations. Lysozyme (30  μ g/mL), but not proteinase K, significantly inhibited biofilm formation (19% inhibition). Treatment of 24-hour-old biofilms of P . aeruginosa isolates with 50 times the minimum inhibitory concentrations (MICs) of ceftazidime and cefepime significantly decreased the biofilm mass by 32.8% and 44%, respectively. Moreover, the exposure of 24-hour-old biofilms of P . aeruginosa isolates to lysozyme (30  μ g/mL) and 50 times MICs of ceftazidime or cefepime resulted in a significant reduction in biofilm mass as compared with the exposure to lysozyme or either antibacterial agent alone. The best antibiofilm effect (49.3%) was observed with the combination of lysozyme (30  μ g/mL) and 50 times MIC of cefepime. The promising antibiofilm activity observed after treatment with 50 times MIC of ceftazidime or cefepime alone or in combination with lysozyme (30  μ g/mL) is indicative of a novel strategy to eradicate pseudomonal biofilms in intravascular devices and contact lenses.